Impact Analysis of Marital Dispensation: Economic Implications and Family Welfare in Social and Legal Context - Ishmah Afiyah; Valijon Ghafurjonovich Macsudov; M Mahmudulhassan; M Muthoifin (Solo International Collaboration and Publication of Social Sciences and Humanities, 2024)
The purpose of this study is to analyze the impact of marital dispensation on the economy and family welfare by considering the related social and legal aspects. The research methods used involve literature studies, statistical data analysis, as well as interviews with legal experts and economists. This study explores various aspects of marital dispensation, including factors influencing the granting of dispensation, legal consequences, and economic impact on the families involved. The results of the analysis show that marital dispensation has a significant impact on the economy and family well-being. On the one hand, dispensation can provide an opportunity for couples to marry despite facing certain obstacles, such as financial problems or age that has not met legal requirements. However, on the other hand, dispensations can also present new challenges, such as economic instability and legal disputes regarding the division of property and the rights and obligations of spouses. In conclusion, a deep understanding of the impact of marriage dispensation is essential in designing more inclusive and equitable social and legal policies. By considering economic and social aspects holistically, more effective strategies can be formulated to improve family welfare and strengthen the social foundation of society as a whole.